HUBUNGAN ANTARA KARAKTERISTIK PETANI DENGAN PRESEPSI PETANI KAKAO DALAM PENERAPAN TEKNOLOGI RORAK DI KECAMATAN BAKUNG KABUPATEN BLITAR - Amilia Arofatul Faiqoh; Yuli Hariyari (UNEJ e-Proceeding, 2018)
Bakung Subdistrict is one of the subdistricts in Blitar Regency. This subdistrict has the potential to increase cocoa production because the area of planting that is owned is quite extensive. This increase in production needs to be balanced with the technology used in cocoa cultivation. Based on the results of a preliminary survey of several cocoa farmers stated that the technology used is the rorak (sediment pit) technology, but its use is still not optimal. Initially the application of this technology was applied by all farmers, then in the last few years rorak technology has begun to not be implemented by farmers. Based on the description, the researchers wanted to examine the characteristics of cocoa farmers who applied and did not apply technology, the perception of cocoa farmers to the characteristics of rorak technology innovation,and also the relationship between the two using correlation analysis. The sampling method in this study was carried out by purposive sampling. The method of data collection is done by observation, interviews which include primary data and literature studies which are secondary data. The research method used is descriptive and analytical. The results showed that: 1) Characteristics of farmers who applied and did not apply cocoa technology included Education, Age, Number of Family Dependents, Experience, Information Sources, Income, Land Ownership Status and Land Area. 2) The cocoa farmers' perceptions of the five characteristics of the rorak technology, namely a) the relatively high level of profit, with a value of 14.57; b) the level of complexity is high with a value of 12.16; c) the level of conformity is classified as moderate with a value of 7.16; d) the level of rorak probability tested is classified as moderate with a value of 9.42; and e) the level of likelihood that the results are seen as moderate with a value of 6.89. Correlation between perceptions of farmers and farmer characteristics obtained r and sig values. 2 (tailed). The value of r indicates the level of strength of the relationship between two variables and the sig value. 2 (tailed) to see the level of significance. Based on sig. 2 (tailed), namely the variablesource of information, income and significant planting area, while the remainder is education, age, number of family dependents, experience and insignificant land ownership.